2017
DOI: 10.1186/s40468-017-0037-0
|View full text |Cite
|
Sign up to set email alerts
|

Markers’ criteria in assessing English essays: an exploratory study of the higher secondary school certificate (HSCC) in the Punjab province of Pakistan

Abstract: Background: Marking of essays is mainly carried out by human raters who bring in their own subjective and idiosyncratic evaluation criteria, which sometimes lead to discrepancy. This discrepancy may in turn raise issues like reliability and fairness. The current research attempts to explore the evaluation criteria of markers on a national level high stakes examination conducted at 12th grade by three examination boards in the South of Pakistan. Methods: Fifteen markers and 30 students participated in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In contrast, a detailed marking sheet is provided to the paper checkers of O level with an intelligent distribution of marks, which checks the multiple elements of language. Fernandez and Siddiqui (2017) reported that raters are not provided with evaluation criteria in the form of a rubric in scoring an English paper for high stake exam conducted by BISE in Punjab. It also means bypassing the objectives behind designing the paper.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, a detailed marking sheet is provided to the paper checkers of O level with an intelligent distribution of marks, which checks the multiple elements of language. Fernandez and Siddiqui (2017) reported that raters are not provided with evaluation criteria in the form of a rubric in scoring an English paper for high stake exam conducted by BISE in Punjab. It also means bypassing the objectives behind designing the paper.…”
Section: Resultsmentioning
confidence: 99%
“…It is because the students focus more on the use of pen and markers than the content. The students with average or unclear handwriting get low scores even after writing quality content on paper, e.g., the different scorers have different expectations from a good piece of writing to their subjective opinion sometimes works as a central factor affecting the reliability of marking (Fernandez and Siddiqui, 2017). On contrary, O level marking criteria focuses on achievable objectives, i.e., awareness of the candidate about a topic, required points for development and variety of justifications with appropriate tone and register rather than considering handwriting as a basis for awarding scores.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As already discussed, the commonplace holistic bias toward overemphasis upon grammar, spelling, and other organizational and meta-linguistic features and briefly discussed teacher perspectives as a key factor which more heavily affects holistic scoring than rubric scoring (or that of other analytic measures). Fernandez and Siddiqui (2017) also point out that rater scoring differences of writing often result from the severity or leniency of their grading preferences. In their 2017 study of fifteen Pakistani writing raters, the respondents rated the same three essays holistically according to their usual scoring practices.…”
Section: Biasmentioning
confidence: 99%